Determination of carbon dioxide production rates for mammalian cells in 24-well plates. (February 2004) - Yang, Yuansheng; Balcarcel, R. Robert
In this report, we describe a method for the quantitative determination of carbon dioxide production rates of mammalian cells. Custom-made, reusable, optically clear plugs are used to seal the wells of a 24-well plate. These plugs prevent the loss of CO2 produced by the mammalian cells cultured in bicarbonate-free medium. Measurements of pH, total liquid phase CO2, and viable cell density are used to estimate the average CO2 production rate during a 6-h incubation period. Using this method, four chemicals well-characterized in regards to toxicity, 2, 4-dinitrophenol, antimycin A, rotenone, and cyanide, were found to elicit significant changes in CO2 production for given concentrations within 6 h, without inducing a decline in culture viability. Over longer exposure times, similar concentrations caused growth inhibition but not cell death. An assay based on metabolic change corresponding to growth inhibition that is more sensitive than traditional measures of cell death is a feasible complement to existing methods in drug discovery and toxicity testing.